Developing affective learning strategies for science education: A literature review - Nurhayati, Pipih; Fuadiah, Dzikra; Yustiana, Yusi Riska (Jurnal Pijar Mipa, 2023)
This study aims to identify innovative, effective learning strategies in science education through a comprehensive literature review. The research utilized trusted databases, WoS and Scopus, which resulted in 19 scholarly articles that met specific inclusion and exclusion criteria. A total of 509 articles were obtained through keyword identification, then through the screening and eligibility stages, and 19 articles that met the criteria were retrieved. The findings underscore the importance of practical assessment and profiling in gaining valuable insights into students' emotional states and competencies. Moreover, the student-centered approach enhances self-awareness and establishes a deep emotional connection with scientific principles. This study highlights the substantial impact of the educational environment and teacher effectiveness on students' affective experiences, emphasizing the importance of fostering a positive and supportive learning atmosphere. The practical learning strategies identified have the potential to contribute to the advancement of science education by promoting emotional engagement and enhancing students' overall learning experience.